2020
DOI: 10.1186/s12991-020-00288-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency mediates the relationship between dietary patterns and depression: a case–control study

Abstract: Background: Depression is a major contributor to disability-adjusted life years (DALY) lost in the world. Dietary patterns are widely used to investigate diet-disease relations. In the current study, the relationship between dietary patterns and depression was investigated. Besides, the role of serum vitamin D, zinc, magnesium, and total antioxidant capacity as potential mediatory variables was studied. Methods: It was an individually matched case-control study in which 330 depressed and healthy subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
(52 reference statements)
1
9
0
3
Order By: Relevance
“…A meta-analysis study confirmed this relationship [89]. Magnesium is important for psychomotor function in major depression [90], and it is effective in the treatment of depression via glutamate [91], and some neurotransmitter systems [92].…”
Section: -4 Covid-19 Vitamin D Deficiency and Depressionmentioning
confidence: 90%
“…A meta-analysis study confirmed this relationship [89]. Magnesium is important for psychomotor function in major depression [90], and it is effective in the treatment of depression via glutamate [91], and some neurotransmitter systems [92].…”
Section: -4 Covid-19 Vitamin D Deficiency and Depressionmentioning
confidence: 90%
“…5 Os estudos apontam que o risco de desenvolvimento de sintomas depressivos parece ser aumentado em pessoas com hipovitaminose D, assim como a suscetibilidade ao desenvolvimento da depressão. 23 Contudo, outras literaturas apontam para o fato de que essa associação pode ser mera coincidência, influenciada por aspectos como estilo de vida, perfil dietético e comorbidades. 14 Atualmente 3 teorias apoiam a associação da vitamina D com o desenvolvimento de depressão: 1) densidade de receptores da vitamina D em regiões do cérebro associadas com o humor (como córtices pré-frontal e cingulado), 2) papel da vitamina D como modulador da inflamação por seu caráter antioxidativo e 3) propriedades neuroprotetivas da vitamina D. 13…”
Section: Relação Entre a Vitamina D E A Depressãounclassified
“…Está documentado que a vitamina D possui receptores em várias regiões do sistema nervoso central (SNC) , como o córtex pré-frontal, córtex cingulado, amígdala, tálamo, substância nigra, núcleos geniculados laterais, hipotálamo, cerebelo e hipocampo, e por isso, tem uma importante ação no desenvolvimento cerebral e é considerada como um neuroesteróide. 19,23,29 A forma ativa da vitamina D, 1,25-diidroxi-vitamina D (1,25(OH)2D) afeta as emoções e comportamento por ter receptores de vitamina D (VDR) na amígdala, o centro do sistema límbico. 23 Além disso, a 1,25(OH)2D tem função neuroprotetora, ação neuromoduladora, atua na regulação da secreção de fatores neurotróficos cerebrais e na neuroplasticidade.…”
Section: Metabolismo Da Vitamina D E Seu Papel No Organismounclassified
See 1 more Smart Citation
“…Lower vitamin D3 is not only detected in CVD/ATS but also in major depression and perinatal depression (Sotoudeh et al, 2020;Trujillo et al, 2018), whilst vitamin D supplementation has a protective effect in depression (Vellekkatt and Menon, 2019). Increased levels of β-endorphin and Mu opioid receptor (MOR) are not only detected in CVD/UA, but also in major depression (Al-Fadhel et al, 2019;Browne and Lucki, 2019;Callaghan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%